Pharmacokinetics of oral mannitol for bowel preparation for colonoscopy - Giancarla Fiori; Cristiano Spada; Pietro Soru; Gian Eugenio Tontini; Ivana Bravi; Bruno Mario Cesana; Paola Cesaro; Gianpiero Manes; Anna Orsatti; Alberto Prada; Alessandro Quadarella; Mario Schettino; et al. (Wiley, 2022)
Abstract This study aimed to define the pharmacokinetics (PKs) of oral mannitol used as an osmotic laxative for bowel preparation for colonoscopy. The PKs of oral mannitol was evaluated in a substudy as part of a phase II dose‐finding, international, multicenter, randomized, parallel‐group, endoscopist‐blinded study. Patients were randomly assigned to take 50, 100, or 150 g mannitol. Venous blood samples were drawn at baseline (T0), 1 h (T1), 2 h (T2), 4 h (T4), and 8 h (T8) after completion of mannitol self‐administration. The mean mannitol plasma concentrations (mg/ml) were dose‐dependent with a consistent difference among doses. The mean maximum concentration (Cmax) ± SD was 0.63 ± 0.15, 1.02 ± 0.28, and 1.36 ± 0.39 mg/ml, in the three dosage groups, respectively. The mean area under the curve from zero to infinity (AUC0−∞) was 2.667 ± 0.668, 4.992 ± 1.706, and 7.403 ± 3.472 mg/ml*h in the 50, 100, and 150 g mannitol dose groups, respectively. Bioavailability was similar in the three dose groups and was just over 20% (0.243 ± 0.073, 0.209 ± 0.081, and 0.228 ± 0.093 in the 50, 100, and 150 g mannitol dose groups, respectively). The present study showed that the bioavailability of oral mannitol is just over 20% and is similar for the three tested doses (50, 100, and 150 g). The linear increase in Cmax, AUC0−t8, and AUC0−∞ must be considered when choosing the oral mannitol dose for bowel preparation to avoid its systemic osmotic effects.